The United States Bayh-Dole Act and its effect on university technology transfer - Gotkin, Joel (MIPLC studies, 2012)
This publication discusses one of the most influential pieces of legislation relating to technology transfer in the United States: The Bayh-Dole Act. The publication discusses the history that led to the groundbreaking Act, characterizes strengths and weaknesses of the Act from an economic and a policy standpoint, and details the recent Supreme Court Stanford v. Roche case, which may carry implications to technology transfer in the future. The publication also compares technology transfer and the Bayh-Dole Act to technology transfer in other developed and developing countries, comparing and contrasting the technology transfer schemes. Joel Gotkin is an attorney at a large full-service Intellectual Property law firm based near Washington, DC. Joel currently handles the full spectrum of patent prosecution for both domestic and international clients. Joel prosecutes patents in the mechanical, electronic and chemical arts, including patents relating to aircraft and automobiles. Joel's research interests lie in technology licensing, specifically relating to universities and pharmaceutical companies.